Solid-state synthesis of PANI-TiO2 nanocomposite: Investigation of reaction conditions, nature of oxidant and electrical properties - F. Sadegh; A. R. Modarresi-Alam; M. Noroozifar; H. Mansouri-Torshizi (eXPRESS Polymer Letters)
In the present work, polyaniline-titanium (IV) oxide (PANI-TiO2) nanocomposites have been synthesized by solidstate (solvent-free) oxidative polymerization method of aniline as a monomer under green condition using both iron (III) chloride hexahydrate (FeCl3·6H2O) and ammonium peroxydisulfate (APS) as two different type of the oxidants as well as various modes and increasing of the ratios of monomer to oxidant. The structural and morphological of the nanocomposites have been characterized using kinetic and microscopic analysis. The electrical conductivities, cyclic voltammetry, bandgap energy (Eg), and morphology of the nanocomposites are mainly dependent on the type of oxidants and reaction conditions. Also, the nanocomposites were shown electro-active and functional properties. The I–V characteristics of PANI-TiO2 in an Al/(PANI-TiO2)/TiO2/FTO solar cell are achieved by drawing the plot of the I–V curves. It is noted that nanocomposites with different conditions were shown similar FT-IR and UV-Vis spectra with different morphologies. The TEM images in different conditions showed a thin layer of TiO2 nanoparticles in the outer wall of the nanotube when the APS was used as the oxidant, while when the FeCl3 was used as the oxidant, the TiO2 nanoparticles have been distributed on a plantain leaf of PANI matrix. The XRD results confirm completely results obtained from TEM. As a result, the nanocomposites with both methods showed a good P–N junction between TiO2 and PANI.